2015
DOI: 10.1038/onc.2015.450
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress enables Epstein–Barr virus-induced B-cell transformation by posttranscriptional regulation of viral and cellular growth-promoting factors

Abstract: Infection of human B lymphocytes by Epstein-Barr virus (EBV) leads to the establishment of immortalized lymphoblastoid cell lines (LCLs) that are widely used as a model of viral oncogenesis. An early consequence of infection is the induction of DNA damage and activation of the DNA damage response, which limits the efficiency of growth transformation. The cause of the DNA damage remains poorly understood. We have addressed this question by comparing the response of B lymphocytes infected with EBV or stimulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 57 publications
0
37
0
Order By: Relevance
“…21 Others have found that these cells also display elevated reactive oxygen species and telomere dysfunction that may induce ATM pathway activation. 19, 26, 27 Early-infected cells also display aberrant karyotypes, but as infected cells grow out over a period of weeks into LCLs the DNA damage signaling wanes and these cells display stable karyotypes. 28 …”
Section: Introductionmentioning
confidence: 99%
“…21 Others have found that these cells also display elevated reactive oxygen species and telomere dysfunction that may induce ATM pathway activation. 19, 26, 27 Early-infected cells also display aberrant karyotypes, but as infected cells grow out over a period of weeks into LCLs the DNA damage signaling wanes and these cells display stable karyotypes. 28 …”
Section: Introductionmentioning
confidence: 99%
“…EBV latency genes play an important role in gastric cancer by independently promoting genomic instability that triggers DNA damage by abnormally regulating cell cycle machinery and DNA repair of infected cells. Exposure of EBV-infected cells correlates with increased DNA damage induced by ROS-induced NOX and NADPH oxidase [138]. Several studies demonstrated that oxidative stress facilitates EBV-induced B-cell transformation through posttranscriptional regulation of viral ( LMP1 ) and host ( STAT3 ) genes, which are critical for promoting B-cell immortalisation, malignant transformation, and tumorigenesis [132, 138, 139].…”
Section: Epstein-barr Virus-induced Carcinogenesismentioning
confidence: 99%
“…Exposure of EBV-infected cells correlates with increased DNA damage induced by ROS-induced NOX and NADPH oxidase [138]. Several studies demonstrated that oxidative stress facilitates EBV-induced B-cell transformation through posttranscriptional regulation of viral ( LMP1 ) and host ( STAT3 ) genes, which are critical for promoting B-cell immortalisation, malignant transformation, and tumorigenesis [132, 138, 139]. IFI16 inflammasome with adaptor ASC protein was shown to be activated upon sensing of latent EBV infection in all types of latency, and this leads to induction of IL-1 β , IL-18, and IL-33 maturation [140].…”
Section: Epstein-barr Virus-induced Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The immortalization of normal B-cells into the Daudi cell line involves the cellular transformation termed Latency III [ 2,3 ]. This is mediated by EBV proteins, including five nuclear proteins (EBNA-1, -2, -3, -5, and -6) and one latent membrane protein (LMP-1) [ 4,5 ]. For example, Epstein-Barr nuclear antigen 1 (EBNA 1), a regularly detected protein of all EBV-associated malignancies, transcriptionally activates the expression of nicotinamide adenine dinucleotide phosphate-oxidase (NADPH) oxidase 2 (NOX2), a key generator of reactive oxygen species (ROS) that is elevated under Latency III [ 6,7 ].…”
Section: Introductionmentioning
confidence: 99%